The Berenstain bears and the bad dream (First Time Books Berenstain Bears, ,, 2012)
After viewing a scary movie about the Spacegrizzlies, Brother Bear has a nightmare.

You've been warned (Little, Brown and Company, Little, Brown and Co, Books on Tape, 2007)
Kristin Burns has lived her life by the philosophy "Don't think, just shoot" -- pictures, that is. Struggling to make ends meet, she works full-time as the nanny for the fabulously wealthy Turnbull family, looking after their two wonderful children and waiting for her glamorous life as a New York photographer to begin. When her photographs are considered by an elite Manhattan art gallery, it seems she might finally get the chance that will start her career. But Kristin has a major distraction: forbidden love. The man of her dreams is almost hers for keeps. Breathless with an inexhaustible passion and the excitement of being within reach of her goals, Kristen ignores all signs of catastrophe brewing. Fear exists for a reason. And Kristin can only dismiss the warnings for so long. Searching desperately for the truth through the lens of her camera, she can only hope that it's not too late.

The nightmare thief (Nightmare thief, 1,, 2021)
When Maren breaks the strict rules of her family's dream shop to help her comatose sister, she is caught and blackmailed by a woman with evil plans for the town of Rockpool Bay.--

Fly Guy and the Frankenfly (Fly Guy, 13,, 2013)
Buzz has a nightmare that his best friend Fly Guy has created a gigantic Frankenfly monster.

Invisible (Invisible, 1,, 2014)
"Everyone thinks Emmy Dockery is crazy. Obsessed with finding the link between hundreds of unsolved cases, Emmy has taken leave from her job as an FBI researcher. Now all she has are the newspaper clippings that wallpaper her bedroom, and her recurring nightmares of an all-consuming fire. Not even Emmy's ex-boyfriend, field agent Harrison 'Books' Bookman, will believe her that hundreds of kidnappings, rapes, and murders are all connected. That is, until Emmy finds a piece of evidence he can't afford to ignore. More murders are reported by the day -- and they're all inexplicable. No motives, no murder weapons, no suspects. Could one person really be responsible for these unthinkable crimes?" -- Provided by publisher.

Early riser (Viking, Books on Tape, 2019)
"Imagine a world where all humans must hibernate through a brutally cold winter, their bodies dangerously close to death as they enter an ultra-low metabolic state of utterly dreamless sleep. All humans, that is, apart from the Winter Consuls, a group of officers who diligently watch over the vulnerable sleeping citizens. Charlie Worthing is a novice, chosen by a highflying hero Winter Consul to accompany him to the Douzey, a remote sector in the middle of Wales, to investigate a dream which is somehow spreading amongst those in the hibernational state, causing paranoia, hallucination and a psychotic episode that can end in murder. Worthing has been trained to deal with Tricksy Nightwalkers whose consciousness has been eroded by hibernation, leaving only one or two skills and an incredible hunger; he's been trained to stay alive through the bleakest and loneliest of winters - but he is in no way prepared for what awaits him in Sector Twelve. There are no heroes in Winter, Worthing has been told. And he's about to find out why."--Publisher's description.

The Bright Lands: a novel (Harlequin Audio, Hanover Square Press, 2020)
"The town of Bentley holds two things dear: its football, and its secrets. But when star quarterback Dylan Whitley goes missing, an unremitting fear grips this remote corner of Texas. Joel Whitley was shamed out of conservative Bentley ten years ago, and while he's finally made a life for himself as a gay man in New York, his younger brother's disappearance soon brings him back to a place he thought he'd escaped for good. Meanwhile, Sheriff's Deputy Starsha Clark stayed in Bentley; Joel's return brings back painful memories -- not to mention questions -- about her own missing brother. And in the high school hallways, Dylan's friends begin to suspect that their classmates know far more than they're telling the police. Together, these unlikely allies will stir up secrets their town has long tried to ignore, drawing the attention of dangerous men who will stop at nothing to see that their crimes stay buried. But no one is quite prepared to face the darkness that's begun to haunt their nightmares, whispering about a place long thought to be nothing but an urban legend: an empty night, a flicker of light on the horizon -- The Bright Lands. Shocking, twisty and relentlessly suspenseful, John Fram's debut is a heart-pounding story about old secrets, modern anxieties and the price young men pay for glory." -- Dust jacket flap.

The night bear (Andersen Press USA, 2019)
Each night, the night bear heads into town and eats his favorite food--children's nightmares--but one day finds a dream in the garbage that does not taste right to him.

The speaker (Book two of Sea of ink and gold, ,, 2017)
"Sefia and Archer's adventure continues as Archer searches for a way to combat his nightmares of his time with the impressors and Sefia becomes more and more consumed by her study of the Book"--

Pooh's bad dream (My very first Winnie the Pooh, ,, 1998)
Description Not Provided

Monster hunters (Nightmare Academy, 1,, 2007)
Rescued from a very sheltered life, thirteen-year-old Charlie learns that the monsters of his nightmares are real when he becomes a student at Nightmare Adademy and begins training to harness his powers to fight terrible creatures and return them to the Netherworld.

The sleepwalkers (Candlewick Press, 2013)
The retiring Sleepwalkers, guardians against nightmares, train three intrepid recruits to take their places, an effort that pits the young heroes against daunting dream hazards.

Don't stay up late (Stine R. L, ,, 2015)
Ever since a car accident killed her father and gave her a severe concussion, high school junior Lisa's been plagued by nightmares and hallucinations, and when she accepts a babysitting job in hopes it will banish the disturbing images, she faces new terror as she begins to question exactly who--or what--she's babysitting.

Gwendy's final task (Gwendy, 03,, 2022)
"When Gwendy Peterson was twelve, a mysterious stranger named Richard Farris gave her a mysterious box for safekeeping. It offered treats and vintage coins, but it was dangerous. Pushing any of its seven colored buttons promised death and destruction. Years later, the button box entered Gwendy's life again. A successful novelist and a rising political star, she was once again forced to deal with the temptation that box represented. Now, evil forces seek to possess the button box and it is up to Senator Gwendy Peterson to keep it from them. At all costs. But where can you hide something from such powerful entities? In GWENDY'S FINAL TASK, 'horror giants' (Publishers Weekly) Stephen King and Richard Chizmar take us on a journey from Castle Rock to another famous cursed Maine city to the MF-1 space station, where Gwendy must execute a secret mission to save the world. And, maybe, all worlds." -- Provided by publisher.

Murder at Sunrise Lake (Berkley, an imprint of Penguin Random House, 2021)
"Stella Harrison thought she had gotten away from the traumas of her past. Running the Sunrise Lake Resort high in the Sierra Nevada mountains has brought her peace, even though she doesn't truly share her quiet life with anyone. Not even Sam, the hired handyman who notices everything and always seems to know exactly what she needs. Stella doesn't know anything about Sam's past, but somehow over the last two years his slow, steady presence has slipped past her defenses. Still, she knows she can't tell him about her recent premonitions. So far there's been no murder. No body. No way to prove what is about to happen without destroying the life she has built for herself. But a killer is out there. And Stella knows that this time she'll do whatever it takes to stop him." -- Dust jacket flap.